Implementation of the COVID-19 laboratory testing certification program (CoLTeP), Zimbabwe, 2021 - Tendai Chipendo; Takudzwa Marembo; Clayton Munemo; Humphrey Chituri; Edwin Shumba; Donewell Bangure; Talkmore Maruta (Pubmed Central, 2023)
Abstract